School Lunch Take up and Attainment in Primary and Secondary Schools in England - Nelson, Michael; Gibson, Karen; Nicholas, Jo (Frontiers in Public Health, 2015)
Hypothesis: Average levels of attainment in primary and secondary schools in England in 2010 and 2011 are positively associated with changes in average school lunch take up between 2008-2009 and 2010-2011. Subjects/Methods: Average school lunch take up and attainment data were available for 2009-2011 for primary and secondary sectors in a minimum of 106 local authorities (LA) in England and 853 individual primary schools in six LAs. Associations between attainment at 11-12y (primary) and 15-16y (secondary) and changes in school lunch take up were tested for using multilevel analysis, multiple regression, and cross-tabulation (chi-squared analysis). Results: At school level, attainment at 11-12y in 2010 and 2011 showed nine positive and 12 negative associations with changes in school lunch take up between 2009 and 2011. At LA level, average attainment at 15-16y in 2011 was associated with changes in total school lunch take up in 2010-2011 (p=0.034). Cross-tabulation of changes in attainment 2010-2011 (above or below median) were positively associated with changes in total school lunch take up between 2009-2011, by quartiles (Chi-squared=11.041, df=3, p=0.012). Conclusions: Attainment at secondary level in England is statistically significantly associated with increases in healthier school lunch take up. Results in the primary sector are not consistent.